2020
DOI: 10.3390/foods9111658
|View full text |Cite
|
Sign up to set email alerts
|

Zn, Cu, and Fe Concentrations in Dehydrated Herbs (Thyme, Rosemary, Cloves, Oregano, and Basil) and the Correlation with the Microbial Counts of Listeria monocytogenes and Other Foodborne Pathogens

Abstract: Zn, Cu, and Fe concentrations were measured in dehydrated herbs (thyme, rosemary, cloves, oregano, and basil) marketed in bulk or packaged in glass or polyethylene terephthalate (PET). Microbial counts of Listeria monocytogenes and other five foodborne pathogens were also checked when herbs were previously added to the growing media. The highest mean concentrations were found in basil for Zn and Cu, and in thyme and basil for Fe; the lowest ones for these minerals were in cloves (p < 0.05). Basil had signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 54 publications
1
11
1
Order By: Relevance
“…As noted in a previous study [ 3 ], basil is the spice that presented higher microbial counts for most of the studied microorganisms.…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…As noted in a previous study [ 3 ], basil is the spice that presented higher microbial counts for most of the studied microorganisms.…”
Section: Resultssupporting
confidence: 68%
“…The samples were analyzed microbiologically on the collection day. Full information on the characteristic of sampling of dried spices considered in this study has been previously reported elsewhere [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations